A method for preparing a carbon cloth electrode for a vanadium liquid flow battery

By introducing rare earth-doped NiCo-MOF material on the carbon cloth for vanadium flow battery and undergoing plasma treatment and high-temperature calcination, the problem of insufficient catalytic activity and conductivity of the carbon cloth electrode is solved, and the performance of the battery is significantly improved.

CN119419290BActive Publication Date: 2025-04-11HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510013740.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The untreated carbon cloth electrode has poor catalytic activity and conductivity in vanadium flow cells, resulting in low voltage efficiency, energy efficiency and electrolyte utilization.

Method used

The reactive activity and conductivity of the carbon cloth are improved by introducing rare earth-doped NiCo-MOF material onto the carbon cloth, and undergoing plasma treatment and high-temperature calcination.

Benefits of technology

The catalytic performance and electrochemical reaction area of ​​the carbon cloth are improved, and the voltage efficiency, energy efficiency and electrolyte utilization rate of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419290B_ABST
    Figure CN119419290B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of all-vanadium flow battery electrodes, and discloses a method for preparing a carbon cloth electrode for a vanadium flow battery, comprising the following steps: preparing a cobalt-nickel bimetallic organic framework NiCo-MOF by a one-pot method and etching it with plasma, then impregnating it with a rare earth ion solution, drying it, and calcining it at high temperature to obtain a rare earth-doped NiCo-MOF material; adding the rare earth-doped NiCo-MOF material, carbon nanotubes, dispersants, surfactants, stabilizers, and high-temperature crosslinking agents to deionized water to disperse the modified carbon slurry; impregnating the carbon cloth in the modified carbon slurry, drying it after impregnation, and sintering it at high temperature to obtain the modified carbon cloth. The present invention introduces a rare earth-doped NiCo-MOF material on the carbon cloth, and calcines it at high temperature. Under the action of H2, the rare earth ions are reduced to form a composite material with NiCo-MOF, thereby improving the crystallinity of the overall material, combining the porosity of the MOF material with the high catalytic activity of the rare earth, and thus improving the reaction activity of the carbon cloth and the battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of all-vanadium liquid flow battery electrodes, and in particular to a method for preparing a carbon cloth electrode for a vanadium liquid flow battery. Background Art

[0002] In recent years, all-vanadium redox flow batteries have become the focus of new energy storage batteries. They have the advantages of independent capacity, high power, long life, deep discharge and no emission pollution. They can be used as supporting energy storage devices in the power generation process of renewable energy such as wind power and solar energy, and can also achieve frequency and peak regulation in the power grid system. They are suitable for electrochemical energy storage devices for large-scale energy storage.

[0003] The electrode materials used in vanadium flow batteries have the best electrical properties. They are porous carbon three-dimensional electrode materials such as graphite felt or carbon felt. They are woven from carbon fibers, have good mechanical strength, and their real specific surface area is much larger than their geometric surface area. They can provide a large electrochemical reaction area. In order to reduce flow resistance, the thickness of graphite felt is usually not less than 2.5 mm. The greater the thickness, the greater the ohmic resistance, which limits the battery performance. The ultra-thin thickness of the carbon cloth electrode can effectively reduce ohmic polarization and improve battery performance. However, untreated carbon cloth electrodes usually have poor catalytic activity and conductivity, resulting in low voltage efficiency, energy efficiency, and electrolyte utilization. In order to solve this problem, scientists have been seeking ways to improve battery energy efficiency and design a simple and high-performance electrode. In addition, the use of high-performance electrode materials is one of the effective ways to reduce the investment cost of all-vanadium flow batteries. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a method for preparing a carbon cloth electrode for a vanadium liquid flow battery.

[0005] A method for preparing a carbon cloth electrode for a vanadium liquid flow battery comprises the following steps:

[0006] Step S1, preparing a cobalt-nickel bimetallic organic framework NiCo-MOF by a one-pot method and etching it by plasma;

[0007] Step S2, immersing the etched NiCo-MOF in a rare earth ion solution, drying it, and then performing a high-temperature calcination treatment to obtain a rare earth-doped NiCo-MOF material;

[0008] Step S3, adding rare earth doped NiCo-MOF material, carbon nanotubes, dispersant, surfactant, stabilizer and high temperature crosslinking agent into deionized water, dispersing them evenly, and obtaining modified carbon slurry;

[0009] Step S4, dipping the carbon cloth in the modified carbon slurry, drying it in an oven after dipping, and then performing high-temperature sintering treatment to obtain the modified carbon cloth.

[0010] Preferably, the one-pot preparation method in step S1 is as follows: dissolving trimesic acid (H3BTC), nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) in a mixed solution of N,N-dimethylformamide (DMF), anhydrous ethanol (EtOH) and deionized water (H2O), transferring to a reactor for hydrothermal reaction after ultrasonic treatment, cooling to room temperature after the reaction, washing the precipitate with ethanol, and drying in an oven to obtain NiCo-MOF.

[0011] Preferably, in step S1, the mass ratio of Ni(NO3)2·6H2O and Co(NO3)2·6H2O is 1:9~9:1, the volume ratio of DMF, EtOH and H2O is 1:1:1, the concentrations of Ni(NO3)2·6H2O and Co(NO3)2·6H2O are 1~10 g / L, and the concentration of H3BTC is 1~5 g / L.

[0012] Preferably, in step S1, the ultrasonic treatment frequency is 50-150 Hz, and the time is 10-30 min; the hydrothermal reaction temperature is 80-150° C., and the time is 12-24 h; the drying temperature in the oven is 80-120° C., and the drying time is 2-5 h;

[0013] Preferably, in step S1, the plasma treatment atmosphere is one of Ar, N2, and air, the treatment frequency is 50-150 Hz, and the treatment time is 10-30 min.

[0014] Preferably, in step S2, the method of impregnating the etched NiCo-MOF with a rare earth ion solution is as follows: dissolving NiCo-MOF and a rare earth material in ethanol, mixing them evenly and drying them at 50°C, wherein the rare earth material is one of La(NO3)3, Ce(NO3)3, Pr(NO3)3 and Tb(NO3)3, and the mass ratio of NiCo-MOF to the rare earth material is (5:1) to (1:1).

[0015] Preferably, the high temperature calcination method in step S2 is: heating the dried NiCo-MOF and rare earth material mixture to 700°C at a heating rate of 2-5°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and keeping the temperature for 2-5h to obtain a rare earth-doped NiCo-MOF material.

[0016] Preferably, in step S3, the dispersant is polyvinyl alcohol; the surfactant is sodium dodecylbenzene sulfonate; the stabilizer is one of nano-alumina and nano-silicon dioxide; and the high-temperature cross-linking agent is one of polyvinyl pyrrolidone K15, polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K60, polyvinyl pyrrolidone K90, and polyvinyl pyrrolidone K150.

[0017] Preferably, in step S3, the mass ratio of the components of the modified slurry in step S3 is rare earth-doped NiCo-MOF: carbon nanotubes: dispersant: surfactant: stabilizer: high temperature cross-linking agent: deionized water = 2: (1-10): 0.5: 0.5: 1: 1: 100.

[0018] Preferably, in step S4, the drying temperature is 80-120°C, the drying time is 2-5h, and the high temperature sintering process is: heating up to 250-350°C at a heating rate of 5-10°C / min, and keeping warm for 2-4h.

[0019] The beneficial effects of this application are:

[0020] 1. This application introduces rare earth-doped NiCo-MOF material on carbon cloth. Since NiCo-MOF has rich topological structure and high active sites after high-temperature calcination, and has a large specific surface area, it can improve the reaction activity of carbon cloth and thus improve battery performance.

[0021] 2. The present application performs plasma treatment on the prepared NiCo-MOF material. Plasma technology can form a large number of vacancies, defects or functional groups, which can significantly improve the catalytic performance. At the same time, plasma technology can combine highly active oxygen with metal atoms in the skeleton to produce metal oxides and heteroatom doping or vacancies with low coordination numbers and unsaturated sites, thereby improving the catalytic ability of MOFs and further improving the reaction activity of carbon cloth.

[0022] 3. In the present application, NiCo-MOF is doped with rare earth ions and calcined at high temperature. Under the action of H2, the rare earth ions are reduced to form a composite material with NiCo-MOF, thereby improving the crystallinity of the overall material and combining the porosity of the MOF material with the high catalytic activity of the rare earth, thereby improving the reaction activity of the carbon cloth.

[0023] 4. This application adds a high-temperature cross-linking agent to the carbon slurry to achieve cross-linking during the sintering process, firmly locks the rare earth-doped NiCo-MOF on the carbon cloth, resists electrolyte erosion, improves the stability of the electrode material, and thus improves the capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic diagram of a process for preparing a carbon cloth electrode for a vanadium liquid flow battery according to the present application. DETAILED DESCRIPTION

[0025] The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application or use. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0026] See also Figure 1 A method for preparing a carbon cloth electrode for a vanadium liquid flow battery comprises the following steps:

[0027] Step S1: preparing a cobalt-nickel bimetallic organic framework NiCo-MOF by a one-pot method and etching it with plasma; the one-pot preparation method is as follows: dissolving trimesic acid H3BTC, nickel nitrate hexahydrate Ni(NO3)2·6H2O and cobalt nitrate hexahydrate Co(NO3)2·6H2O in a mixed solution of N,N-dimethylformamide DMF, anhydrous ethanol EtOH and deionized water H2O, and transferring the mixture to a reactor for hydrothermal reaction after ultrasonic treatment. After the reaction is completed, the mixture is cooled to room temperature, washed with ethanol, and dried in an oven to obtain NiCo-MOF; the mass ratio of Ni(NO3)2·6H2O and Co(NO3)2·6H2O is 0.0447 W / m / s. The molar ratio is 1:9~9:1, the volume ratio of DMF, EtOH and H2O is 1:1:1, the concentrations of Ni(NO3)2·6H2O and Co(NO3)2·6H2O are 1~10g / L, and the concentration of H3BTC is 1~5g / L; the ultrasonic treatment frequency is 50~150Hz, and the time is 10~30min; the hydrothermal reaction temperature is 80~150℃, and the time is 12~24h; the drying temperature in the oven is 80~120℃, and the drying time is 2~5h; the plasma treatment atmosphere is one of Ar, N2, and air, the treatment frequency is 50~150Hz, and the treatment time is 10~30min.

[0028] Step S2: The etched NiCo-MOF is immersed in a rare earth ion solution, and then dried and calcined at high temperature to obtain a rare earth-doped NiCo-MOF material; the method for immersing the etched NiCo-MOF in a rare earth ion solution is as follows: NiCo-MOF and a rare earth material are dissolved in ethanol, mixed evenly, and then dried at 50°C, wherein the rare earth material is one of La(NO3)3, Ce(NO3)3, Pr(NO3)3 and Tb(NO3)3, and the mass ratio of NiCo-MOF to the rare earth material is (5:1)~(1:1); the high temperature calcination method is as follows: the dried NiCo-MOF and rare earth material mixture is heated to 700°C at a heating rate of 2~5°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and kept warm for 2~5h to obtain a rare earth-doped NiCo-MOF material.

[0029] Step S3: adding rare earth doped NiCo-MOF material, carbon nanotubes, dispersant, surfactant, stabilizer and high temperature crosslinking agent into deionized water, dispersing them evenly to obtain modified carbon slurry; the dispersant is polyvinyl alcohol; the surfactant is sodium dodecylbenzene sulfonate; the stabilizer is one of nano-alumina and nano-silicon dioxide; the high temperature crosslinking agent is one of polyvinyl pyrrolidone K15, polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K60, polyvinyl pyrrolidone K90 and polyvinyl pyrrolidone K150; the mass ratio of the components of the modified slurry is rare earth doped NiCo-MOF: carbon nanotubes: dispersant: surfactant: stabilizer: high temperature crosslinking agent: deionized water is 2: (1-10): 0.5: 0.5: 1: 1: 100.

[0030] Step S4: The carbon cloth is immersed in the modified carbon slurry, dried in an oven after the immersion, and then subjected to high-temperature sintering treatment to obtain the modified carbon cloth; the carbon cloth drying temperature is 80-120°C, the drying time is 2-5h, and the carbon cloth high-temperature sintering process: the temperature is increased to 250-350°C at a heating rate of 5-10°C / min, and kept warm for 2-4h.

[0031] Example 1: A method for preparing a carbon cloth electrode for a vanadium redox flow battery, comprising the following steps:

[0032] Step S1: prepare 1000 ml of a mixed solution of DMF, EtOH and H2O in a volume ratio of 1:1:1, add 1 g H3BTC, 1 g Ni(NO3)2·6H2O and 9 g Co(NO3)2·6H2O, transfer to a hydrothermal reactor after 50 Hz ultrasonic treatment for 30 min, hydrothermally react at 80°C for 24 h, cool to room temperature, wash the precipitate with ethanol, dry in an oven at 80°C for 5 h to obtain NiCo-MOF, and treat with Ar plasma at a frequency of 50 Hz for 30 min to obtain etched NiCo-MOF;

[0033] Step S2: 5 g of plasma-etched NiCo-MOF and 1 g of La(NO3)3 were dissolved in 500 ml of ethanol, mixed evenly, and dried completely at 50°C. The dried NiCo-MOF and rare earth material mixture was heated to 700°C at a heating rate of 2°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and kept warm for 5 h to obtain La-doped NiCo-MOF material;

[0034] Step S3: adding 2 g La-doped NiCo-MOF, 1 g carbon nanotubes, 0.5 g polyvinyl alcohol, 0.5 g sodium dodecylbenzene sulfonate, 1 g nano-alumina and 1 g polyvinyl pyrrolidone K15 into 100 ml deionized water, dispersing them evenly, and obtaining a modified carbon slurry;

[0035] Step S4: immerse the carbon cloth in the modified carbon slurry, and then dry it in an oven at a temperature of 80°C for 5 hours. The high-temperature sintering process of the carbon cloth is as follows: heat up to 250°C at a heating rate of 5°C / min and keep warm for 4 hours to obtain a modified carbon cloth electrode.

[0036] Example 2: A method for preparing a carbon cloth electrode for a vanadium redox flow battery, comprising the following steps:

[0037] Step S1: prepare 1000 ml of a mixed solution of DMF, EtOH and H2O in a volume ratio of 1:1:1, add 2 g H3BTC, 2 g Ni(NO3)2·6H2O and 10 g Co(NO3)2·6H2O, transfer to a hydrothermal reactor after 60 Hz ultrasonic treatment for 25 min, hydrothermally react at 90°C for 16 h, cool to room temperature, wash the precipitate with ethanol, dry in an oven at 90°C for 4 h to obtain NiCo-MOF, and treat with N2 plasma at a frequency of 80 Hz for 30 min to obtain the etched NiCo-MOF;

[0038] Step S2: 5 g of plasma-etched NiCo-MOF and 2 g of Ce(NO3)3 were dissolved in 500 ml of ethanol, mixed evenly and dried completely at 50°C, and the dried NiCo-MOF and rare earth material mixture was heated to 700°C at a heating rate of 3°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and kept warm for 2 h to obtain Ce-doped NiCo-MOF material;

[0039] Step S3: adding 2 g Ce-doped NiCo-MOF, 2 g carbon nanotubes, 0.5 g polyvinyl alcohol, 0.5 g sodium dodecylbenzene sulfonate, 1 g nano-alumina and 1 g polyvinyl pyrrolidone K30 into 100 ml deionized water, and dispersing them evenly to obtain a modified carbon slurry;

[0040] Step S4: immerse the carbon cloth in the modified carbon slurry, and then dry it in an oven at a temperature of 90°C for 4 hours. The high-temperature sintering process of the carbon cloth is as follows: heat up to 280°C at a heating rate of 10°C / min and keep warm for 3.5 hours to obtain a modified carbon cloth electrode.

[0041] Example 3: A method for preparing a carbon cloth electrode for a vanadium redox flow battery, comprising the following steps:

[0042] Step S1: prepare 1000 ml of a mixed solution of DMF, EtOH and H2O in a volume ratio of 1:1:1, add 3 g H3BTC, 9 g Ni(NO3)2·6H2O and 1 g Co(NO3)2·6H2O, transfer to a hydrothermal reactor after 70 Hz ultrasonic treatment for 20 min, hydrothermally react at 100°C for 20 h, cool to room temperature, wash the precipitate with ethanol, dry in an oven at 100°C for 3.5 h to obtain NiCo-MOF, and treat with air plasma at a frequency of 100 Hz for 20 min to obtain etched NiCo-MOF;

[0043] Step S2: 5 g of plasma-etched NiCo-MOF and 3 g of Pr(NO3)3 were dissolved in 500 ml of ethanol, mixed evenly and dried completely at 50°C, and the dried NiCo-MOF and rare earth material mixture was heated to 700°C at a heating rate of 3°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and kept warm for 3 h to obtain Pr-doped NiCo-MOF material;

[0044] Step S3: adding 2 g of Pr-doped NiCo-MOF, 3 g of carbon nanotubes, 0.5 g of polyvinyl alcohol, 0.5 g of sodium dodecylbenzene sulfonate, 1 g of nano-silica and 1 g of polyvinyl pyrrolidone K60 into 100 ml of deionized water, and dispersing them evenly to obtain a modified carbon slurry;

[0045] Step S4: immerse the carbon cloth in the modified carbon slurry, and then dry it in an oven at a temperature of 100°C for 3 hours. The high-temperature sintering process of the carbon cloth is as follows: heat up to 300°C at a heating rate of 6°C / min and keep warm for 3 hours to obtain a modified carbon cloth electrode.

[0046] Example 4: A method for preparing a carbon cloth electrode for a vanadium redox flow battery, comprising the following steps:

[0047] Step S1: prepare 1000 ml of a mixed solution of DMF, EtOH and H2O in a volume ratio of 1:1:1, add 4 g H3BTC, 8 g Ni(NO3)2·6H2O and 4 g Co(NO3)2·6H2O, transfer to a hydrothermal reactor after 80 Hz ultrasonic treatment for 15 min, hydrothermally react at 120°C for 14 h, cool to room temperature, wash the precipitate with ethanol, and dry in an oven at 110°C for 3 h to obtain NiCo-MOF, and treat with Ar plasma at a frequency of 120 Hz for 15 min to obtain etched NiCo-MOF;

[0048] Step S2: 5 g of plasma-etched NiCo-MOF and 4 g of Tb(NO3)3 were dissolved in 500 ml of ethanol, mixed evenly and dried completely at 50°C, and the dried NiCo-MOF and rare earth material mixture was heated to 700°C at a heating rate of 5°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and kept warm for 2 h to obtain Tb-doped NiCo-MOF material;

[0049] Step S3: adding 2 g of Tb-doped NiCo-MOF, 4 g of carbon nanotubes, 0.5 g of polyvinyl alcohol, 0.5 g of sodium dodecylbenzene sulfonate, 1 g of nano-silica and 1 g of polyvinyl pyrrolidone K90 into 100 ml of deionized water, and dispersing them evenly to obtain a modified carbon slurry;

[0050] Step S4: immerse the carbon cloth in the modified carbon slurry, and then dry it in an oven at a temperature of 110°C for 2 hours. The high-temperature sintering process of the carbon cloth is as follows: heat up to 320°C at a heating rate of 8°C / min and keep warm for 2.5 hours to obtain a modified carbon cloth electrode.

[0051] Example 5: A method for preparing a carbon cloth electrode for a vanadium redox flow battery, comprising the following steps:

[0052] Step S1: prepare 1000 ml of a mixed solution of DMF, EtOH and H2O in a volume ratio of 1:1:1, add 5 g H3BTC, 5 g Ni(NO3)2·6H2O and 5 g Co(NO3)2·6H2O, transfer to a hydrothermal reactor after ultrasonic treatment at 100 Hz for 10 min, hydrothermally react at 130°C for 12 h, cool to room temperature, wash the precipitate with ethanol, dry in an oven at 120°C for 2 h to obtain NiCo-MOF, and treat with N2 plasma at a frequency of 150 Hz for 10 min to obtain etched NiCo-MOF;

[0053] Step S2: 5 g of plasma-etched NiCo-MOF and 5 g of La(NO3)3 were dissolved in 500 ml of ethanol, mixed evenly and dried completely at 50°C, and the dried NiCo-MOF and rare earth material mixture was heated to 700°C at a heating rate of 5°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and kept warm for 2 h to obtain La-doped NiCo-MOF material;

[0054] Step S3: adding 2 g La-doped NiCo-MOF, 9 g carbon nanotubes, 0.5 g polyvinyl alcohol, 0.5 g sodium dodecylbenzene sulfonate, 1 g nano-silica and 1 g polyvinyl pyrrolidone K150 into 100 ml deionized water, and dispersing them evenly to obtain a modified carbon slurry;

[0055] Step S4: immerse the carbon cloth in the modified carbon slurry, and then dry it in an oven at a temperature of 120°C for 2 hours. The high-temperature sintering process of the carbon cloth is as follows: heat up to 350°C at a heating rate of 9°C / min and keep warm for 2 hours to obtain a modified carbon cloth electrode.

[0056] Example 6: A method for preparing a carbon cloth electrode for a vanadium redox flow battery, comprising the following steps:

[0057] Step S1: prepare 1000 ml of a mixed solution of DMF, EtOH and H2O in a volume ratio of 1:1:1, add 2.5 g H3BTC, 4 g Ni(NO3)2·6H2O and 8 g Co(NO3)2·6H2O, transfer to a hydrothermal reactor after 120 Hz ultrasonic treatment for 10 min, hydrothermally react at 150°C for 8 h, cool to room temperature, wash the precipitate with ethanol, and dry in an oven at 110°C for 3 h to obtain NiCo-MOF, and treat with air plasma at a frequency of 120 Hz for 25 min to obtain etched NiCo-MOF;

[0058] Step S2: 5 g of plasma-etched NiCo-MOF and 2.5 g of Ce(NO3)3 were dissolved in 500 ml of ethanol, mixed evenly, and dried completely at 50°C. The dried NiCo-MOF and rare earth material mixture was heated to 700°C at a heating rate of 3°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and kept warm for 5 h to obtain Ce-doped NiCo-MOF material;

[0059] Step S3: adding 2 g Ce-doped NiCo-MOF, 6 g carbon nanotubes, 0.5 g polyvinyl alcohol, 0.5 g sodium dodecylbenzene sulfonate, 1 g nano-alumina and 1 g polyvinyl pyrrolidone K15 into 100 ml deionized water, dispersing them evenly, and obtaining a modified carbon slurry;

[0060] Step S4: immerse the carbon cloth in the modified carbon slurry, and then dry it in an oven at a temperature of 80°C for 5 hours. The high-temperature sintering process of the carbon cloth is as follows: heat up to 250°C at a heating rate of 8°C / min and keep warm for 4 hours to obtain a modified carbon cloth electrode.

[0061] Example 7: A method for preparing a carbon cloth electrode for a vanadium redox flow battery, comprising the following steps:

[0062] Step S1: prepare 1000 ml of a mixed solution of DMF, EtOH and H2O in a volume ratio of 1:1:1, add 2.5 g H3BTC, 2 g Ni(NO3)2·6H2O and 9 g Co(NO3)2·6H2O, transfer to a hydrothermal reactor after ultrasonic treatment at 150 Hz for 10 min, hydrothermally react at 140°C for 10 h, cool to room temperature, wash the precipitate with ethanol, dry in an oven at 90°C for 4 h to obtain NiCo-MOF, and treat with Ar plasma at a frequency of 100 Hz for 25 min to obtain etched NiCo-MOF;

[0063] Step S2: 5 g of plasma-etched NiCo-MOF and 3.5 g of Pr(NO3)3 were dissolved in 500 ml of ethanol, mixed evenly and dried completely at 50°C, and the dried NiCo-MOF and rare earth material mixture was heated to 700°C at a heating rate of 2.5°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and kept warm for 2 h to obtain Pr-doped NiCo-MOF material;

[0064] Step S3: adding 2 g Pr-doped NiCo-MOF, 7 g carbon nanotubes, 0.5 g polyvinyl alcohol, 0.5 g sodium dodecylbenzene sulfonate, 1 g nano-alumina and 1 g polyvinyl pyrrolidone K90 into 100 ml deionized water, and dispersing them evenly to obtain a modified carbon slurry;

[0065] Step S4: immerse the carbon cloth in the modified carbon slurry, and then dry it in an oven at a temperature of 120°C for 2 hours. The high-temperature sintering process of the carbon cloth is as follows: heat up to 350°C at a heating rate of 10°C / min and keep warm for 2.5 hours to obtain a modified carbon cloth electrode.

[0066] Example 8: A method for preparing a carbon cloth electrode for a vanadium redox flow battery, comprising the following steps:

[0067] Step S1: prepare 1000 ml of a mixed solution of DMF, EtOH and H2O in a volume ratio of 1:1:1, add 4.5 g H3BTC, 3 g Ni(NO3)2·6H2O and 9 g Co(NO3)2·6H2O, transfer to a hydrothermal reactor after ultrasonic treatment at 100 Hz for 20 min, hydrothermally react at 120°C for 18 h, cool to room temperature, wash the precipitate with ethanol, dry in an oven at 80°C for 4 h to obtain NiCo-MOF, and treat with Ar plasma at a frequency of 90 Hz for 20 min to obtain etched NiCo-MOF;

[0068] Step S2: 5 g of plasma-etched NiCo-MOF and 5 g of Tb(NO3)3 were dissolved in 500 ml of ethanol, mixed evenly and dried completely at 50°C, and the dried NiCo-MOF and rare earth material mixture was heated to 700°C at a heating rate of 4°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and kept warm for 5 h to obtain Tb-doped NiCo-MOF material;

[0069] Step S3: adding 2 g Tb-doped NiCo-MOF, 8 g carbon nanotubes, 0.5 g polyvinyl alcohol, 0.5 g sodium dodecylbenzene sulfonate, 1 g nano-alumina and 1 g polyvinyl pyrrolidone K15 into 100 ml deionized water, dispersing them evenly, and obtaining a modified carbon slurry;

[0070] Step S4: immerse the carbon cloth in the modified carbon slurry, and then dry it in an oven at a temperature of 80°C for 5 hours. The high-temperature sintering process of the carbon cloth is as follows: heat up to 250°C at a heating rate of 5°C / min and keep warm for 4 hours to obtain a modified carbon cloth electrode.

[0071] Example 9: A method for preparing a carbon cloth electrode for a vanadium redox flow battery, comprising the following steps:

[0072] Step S1: prepare 1000 ml of a mixed solution of DMF, EtOH and H2O in a volume ratio of 1:1:1, add 2 g H3BTC, 9 g Ni(NO3)2·6H2O and 3 g Co(NO3)2·6H2O, transfer to a hydrothermal reactor after 80 Hz ultrasonic treatment for 25 min, hydrothermally react at 100°C for 16 h, cool to room temperature, wash the precipitate with ethanol, dry in an oven at 100°C for 3 h to obtain NiCo-MOF, and treat with Ar plasma at a frequency of 100 Hz for 20 min to obtain etched NiCo-MOF;

[0073] Step S2: 5 g of plasma-etched NiCo-MOF and 5 g of La(NO3)3 were dissolved in 500 ml of ethanol, mixed evenly, and dried completely at 50°C. The dried NiCo-MOF and rare earth material mixture was heated to 700°C at a heating rate of 5°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and kept warm for 5 h to obtain La-doped NiCo-MOF material;

[0074] Step S3: adding 2 g La-doped NiCo-MOF, 9 g carbon nanotubes, 0.5 g polyvinyl alcohol, 0.5 g sodium dodecylbenzene sulfonate, 1 g nano-alumina and 1 g polyvinyl pyrrolidone K15 into 100 ml deionized water, and dispersing them evenly to obtain a modified carbon slurry;

[0075] Step S4: immerse the carbon cloth in the modified carbon slurry, and then dry it in an oven at a temperature of 80°C for 4 hours. The high-temperature sintering process of the carbon cloth is as follows: heat up to 350°C at a heating rate of 5°C / min and keep warm for 3 hours to obtain a modified carbon cloth electrode.

[0076] Embodiment 10: A method for preparing a carbon cloth electrode for a vanadium redox flow battery, comprising the following steps:

[0077] Step S1: prepare 1000 ml of a mixed solution of DMF, EtOH and H2O in a volume ratio of 1:1:1, add 3.5 g H3BTC, 10 g Ni(NO3)2·6H2O and 2 g Co(NO3)2·6H2O, transfer to a hydrothermal reactor after 90 Hz ultrasonic treatment for 30 min, hydrothermally react at 80°C for 20 h, cool to room temperature, wash the precipitate with ethanol, dry in an oven at 100°C for 5 h to obtain NiCo-MOF, and treat with Ar plasma at a frequency of 50 Hz for 25 min to obtain etched NiCo-MOF;

[0078] Step S2: 5 g of plasma-etched NiCo-MOF and 3.5 g of La(NO3)3 were dissolved in 500 ml of ethanol, mixed evenly and dried completely at 50°C, and the dried NiCo-MOF and rare earth material mixture was heated to 700°C at a heating rate of 3°C / min in an atmosphere of H2 / Ar (volume ratio 1:1), and kept warm for 5 h to obtain La-doped NiCo-MOF material;

[0079] Step S3: adding 2 g La-doped NiCo-MOF, 10 g carbon nanotubes, 0.5 g polyvinyl alcohol, 0.5 g sodium dodecylbenzene sulfonate, 1 g nano-silica and 1 g polyvinyl pyrrolidone K15 into 100 ml deionized water, and dispersing them evenly to obtain a modified carbon slurry;

[0080] Step S4: immerse the carbon cloth in the modified carbon slurry, and then dry it in an oven at a temperature of 80°C for 5 hours. The high-temperature sintering process of the carbon cloth is as follows: heat up to 250°C at a heating rate of 10°C / min and keep warm for 4 hours to obtain a modified carbon cloth electrode.

[0081] Comparative Example 1: The preparation process of this comparative example is different from that of Example 1 only in that no rare earth-doped NiCo-MOF is added to the carbon slurry.

[0082] Comparative Example 2: The preparation process of this comparative example is different from that of Example 1 only in that only NiCo-MOF material is added to the carbon slurry.

[0083] Comparative Example 3: The preparation process of this comparative example is different from that of Example 1 only in that no plasma treatment is used after the preparation of NiCo-MOF.

[0084] Comparative Example 4: This comparative example is a blank control group, that is, an untreated blank carbon cloth is used.

[0085] The carbon cloth obtained in Examples 1-10 and Comparative Examples 1-4 was cut into a size of 3 cm*3 cm, copper plates were placed at both ends, and a low resistance tester was used to clamp the copper plates at both ends to test the resistance value at 20% deformation. Contact resistance = resistance value - material body resistance.

[0086] The carbon cloths prepared in the embodiment and the comparative example were assembled into battery stacks and charged and discharged under the same test conditions, and the battery coulombic efficiency, voltage efficiency, energy efficiency, capacity retention rate after 100 cycles and electrolyte utilization rate were recorded, where electrolyte utilization rate = actual discharge capacity / theoretical discharge capacity. The test results are shown in Table 1:

[0087] Table 1: Electrode and battery performance test table

[0088]

[0089] It can be seen that by comparing Example 1 with Comparative Example 1, it can be seen that since the rare earth-modified NiCo-MOF has rich topological structures and high active sites and a large specific surface area, the conductivity of the carbon cloth can be improved and its electrochemical performance can be improved, and no rare earth-modified NiCo-MOF is added in Comparative Example 1, so the voltage efficiency is slightly reduced; by comparing Example 1 with Comparative Example 2, it can be seen that NiCo-MOF is doped with a rare earth material and calcined at a high temperature. Under the action of H2, the rare earth ions are reduced to form a composite material with NiCo-MOF, thereby improving the crystallinity of the overall material, combining the porosity of the MOF material with the high catalytic activity of the rare earth, thereby improving the reaction activity of the carbon cloth, and in Comparative Example 2, only NiCo-MOF material is not added, so the performance is slightly worse; by comparing Example 1 with Comparative Example 3, it can be seen that the NiCo-MOF prepared without plasma treatment in Comparative Example 3, plasma technology can form a large number of vacancies, defects or functional groups, which can significantly improve the catalytic performance, so the voltage efficiency is slightly reduced.

[0090] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a carbon cloth electrode for a vanadium redox flow battery, characterized in that: The following steps are involved: Step S1: one-pot preparation of cobalt-nickel bimetallic organic framework NiCo-MOF and plasma etching; Step S2: The etched NiCo-MOF is immersed in a rare earth ion solution, dried, and then subjected to high-temperature calcination to obtain a rare earth-doped NiCo-MOF material; the high-temperature calcination method is: the dried NiCo-MOF and rare earth material mixture is heated to 700°C at a heating rate of 2-5°C / min in an atmosphere of a mixed gas composed of hydrogen and argon in a volume ratio of 1:1, and kept warm for 2-5 hours to obtain a rare earth-doped NiCo-MOF material; Step S3: adding rare earth doped NiCo-MOF material, carbon nanotubes, dispersant, surfactant, stabilizer and high temperature crosslinking agent into deionized water, dispersing evenly, and obtaining modified carbon slurry; the dispersant is polyvinyl alcohol; the surfactant is sodium dodecylbenzene sulfonate; the stabilizer is one of nano-alumina and nano-silicon dioxide; the high temperature crosslinking agent is one of polyvinyl pyrrolidone K15, polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K60, polyvinyl pyrrolidone K90, and polyvinyl pyrrolidone K150; Step S4: The carbon cloth is immersed in the modified carbon slurry, dried in an oven after the immersion, and then subjected to high-temperature sintering treatment to obtain the modified carbon cloth; the drying temperature is 80-120°C, the drying time is 2-5h, and the high-temperature sintering process is: the temperature is increased to 250-350°C at a heating rate of 5-10°C / min, and the temperature is kept for 2-4h.

2. The method for preparing a carbon cloth electrode for a vanadium redox flow battery according to claim 1, characterized in that: The one-pot preparation method in step S1 is: dissolving trimesic acid, nickel nitrate hexahydrate and cobalt nitrate hexahydrate in a mixed solution of N,N-dimethylformamide, anhydrous ethanol and deionized water, transferring to a reactor for hydrothermal reaction after ultrasonic treatment, cooling to room temperature after the reaction, washing the precipitate with ethanol, and drying in an oven to obtain NiCo-MOF.

3. The method for preparing a carbon cloth electrode for a vanadium redox flow battery according to claim 1, characterized in that: In the step S1, the plasma treatment atmosphere is one of Ar, N2, and air, the treatment frequency is 50-150 Hz, and the treatment time is 10-30 min.

4. The method for preparing a carbon cloth electrode for a vanadium redox flow battery according to claim 2, characterized in that: The mass ratio of the nickel nitrate hexahydrate to the cobalt nitrate hexahydrate is 1:9-9:1, the volume ratio of N,N-dimethylformamide, anhydrous ethanol and deionized water is 1:1:1, the concentrations of the nickel nitrate hexahydrate and the cobalt nitrate hexahydrate are 1-10 g / L, and the concentration of trimesic acid is 1-5 g / L.

5. The method for preparing a carbon cloth electrode for a vanadium redox flow battery according to claim 2, characterized in that: The ultrasonic treatment frequency is 50-150 Hz, and the time is 10-30 min; the hydrothermal reaction temperature is 80-150° C., and the time is 12-24 h; the drying temperature in the oven is 80-120° C., and the drying time is 2-5 h.

6. The method for preparing a carbon cloth electrode for a vanadium redox flow battery according to claim 1, characterized in that: The method of immersing the etched NiCo-MOF in a rare earth ion solution in step S2 is as follows: dissolving NiCo-MOF and a rare earth material in ethanol, mixing them evenly and drying them at 50° C., wherein the rare earth material is one of La(NO3)3, Ce(NO3)3, Pr(NO3)3 and Tb(NO3)3, and the mass ratio of NiCo-MOF to the rare earth material is (5:1) to (1:1).

7. The method for preparing a carbon cloth electrode for a vanadium redox flow battery according to claim 1, characterized in that: The mass ratio of the components of the modified slurry in step S3 is rare earth-doped NiCo-MOF: carbon nanotubes: dispersant: surfactant: stabilizer: high temperature cross-linking agent: deionized water = 2: (1-10): 0.5: 0.5: 1: 1: 100.

Citation Information

Patent Citations

  • Rare earth metal doped MOF structure oxygen electrocatalyst and preparation method thereof

    CN114665108A

  • Carbon cloth loaded rare earth oxide Eu2O3 modified NiCo alloy hydrogen evolution catalyst as well as preparation method and application thereof

    CN118704031A